Personality and Hypothalamic–Pituitary–Adrenal Axis in Older Men and Women - Montoliu, Teresa; Hidalgo, Vanesa; Salvador, Alicia (Frontiers in Psychology, 2020)
Personality has been related to health and mortality risk, which has created interest in the biological pathways that could explain this relationship. Although a dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis has been associated with health outcomes and aging, few studies have explored the association between personality and HPA axis functioning in older adults. In addition, it has been suggested that sex could moderate the relationship between personality and HPA axis functioning. Thus, our aim was to analyze the relationship between the big five personality traits and the diurnal cortisol pattern in older adults, as well as sex differences in this relationship. To do so, 79 older people (40 men and 39 women) from 59 to 81 years old (M = 69.19, SD = 4.60) completed the NEO-Five-Factor Inventory (FFI) to measure neuroticism, conscientiousness, extraversion, openness, and agreeableness. Saliva samples were provided on three consecutive days (awakening; 15, 30, and 45 min post-awakening; and bedtime) in order to analyze the diurnal cortisol pattern and, specifically, two cortisol indexes: the cortisol awakening response (CAR) and the diurnal cortisol slope (DCS). Results showed that neuroticism and conscientiousness moderated the diurnal cortisol pattern. Thus, individuals with higher neuroticism and lower conscientiousness scores showed higher bedtime cortisol levels, suggesting a less healthy diurnal cortisol pattern. Regarding the cortisol indexes, higher neuroticism and lower conscientiousness were related to greater CAR and DCS. Sex moderated the association between extraversion and the DCS. Specifically, higher extraversion was related to a lower DCS only in women. Openness and agreeableness were not related to the diurnal cortisol pattern. In conclusion, our results show that in older adults, neuroticism is a vulnerability factor for HPA axis dysregulation, with possible adverse effects on health. By contrast, conscientiousness, and extraversion only in women, appear to be protective factors of HPA axis functioning, with potential beneficial effects on health.